AKURASI POSISI GUNUNG SALAK SEBAGAI ARAH KIBLAT BAGI MASYARAKAT CIGOMBONG BOGOR PERSPEKTIF ILMU FALAK DAN FIKIH - Asathin, Muhamad Wildan; Kusdiyana, Kusdiyana; Bustomi, Ilham (Mahkamah : Jurnal Kajian Hukum Islam, 2025)
Muslims are commanded to worship, including prayer. In performing prayer, there are rules that have been determined and must be fulfilled, namely pillars and conditions. Facing the Qibla is one of the valid requirements in prayer, the Qibla is the closest direction to the Baitullah (Kaaba). For people who live close to the Kaaba, facing the Qibla is not a problem, but sometimes it can be a problem for people who live far from the Kaaba. One of them in Indonesia, precisely in Cigombong District, Bogor Regency, there is a unique phenomenon in the form of local wisdom regarding the direction of the Qibla, the community has a belief in Mount Salak as a benchmark for the direction of the Qibla. The formulation of the problem in this study is "What is the background to the emergence of the community's belief that Mount Salak is a benchmark for the direction of the Qibla" and "How accurate is the position of Mount Salak towards the Kaaba in Cigombong District, Bogor". This research uses a qualitative method, the data collected is through observation, interviews, documentation, and literature studies. And the tools used in this accuracy test measurement are Mizwala & Google Earth software. The results of this study, that the background of the Cigombong community's belief in Mount Salak as a benchmark for the direction of the Qibla are: the position of Mount Salak which is in the west, and the Cigombong community used to understand that if facing the Qibla it was limited to facing the kulon (west) direction which coincides with the position of Mount Salak and secondly because of local wisdom inherited from ancestors to the local community. A belief that was formed before the existence of a compass and other tools that can be used to determine the direction of the Qibla. Then in the accuracy test of Mount Salak: it turned out to be true, that Mount Salak is in the same direction as the Kaaba. However, Mount Salak or any mountain cannot be used as a benchmark in facing the direction of the Qibla. Because basically this mountain is a part of the earth that is towering and large, meaning that with the large body of the mountain, it is very impossible to face exactly the direction of the Qibla (Kaaba), and it is also unknown, that which point on the part of the mountain is exactly facing the direction of the Kaaba.